2007
DOI: 10.3184/095422907x236100
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of some heavy metals in coal fly ash

Abstract: Selected heavy metals Cu, Ni, Zn and Pb were studied in two different types of coal fly ash samples, dyke and field, collected from Badarpur Thermal Power Station, Delhi, India for their total metal concentration as well as geochemical differentiation in different chemical fraction namely exchangeable, easily reducible or Fe -Mn bound, organic or sulfide bound and residual fractions. The total concentration of heavy metals in both types of fly ash samples followed the order Cr4Zn4Pb4Ni4Cu. Among the two types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The levels of Nickel ranged from 18.85 to 73.70% with an average of 51.58%. This predominance of inactive forms of nickel is in agreement with other studies of contaminated soils (Gupta and Chen 1975;Tessier and Campbell, 1980;Ma and Rao, 1997;Abeh et al, 2007;Chaudhary and Banerjee, 2007;Osakwe, 2010). Norrish, (1975 observed that nickel is commonly occluded by silicate during soil weathering.…”
Section: Okolie Lucky Precioussupporting
confidence: 92%
See 1 more Smart Citation
“…The levels of Nickel ranged from 18.85 to 73.70% with an average of 51.58%. This predominance of inactive forms of nickel is in agreement with other studies of contaminated soils (Gupta and Chen 1975;Tessier and Campbell, 1980;Ma and Rao, 1997;Abeh et al, 2007;Chaudhary and Banerjee, 2007;Osakwe, 2010). Norrish, (1975 observed that nickel is commonly occluded by silicate during soil weathering.…”
Section: Okolie Lucky Precioussupporting
confidence: 92%
“…Lead ranged from 9.72 to 14.265% with an average of 12.24%. Many studies reported predominance of lead in this fraction (Chaudhary and Banerjee, 2007;Asagba et al, 2007;Osakwe and Egharevba, 2008;Osakwe et al, 2012). The levels of Nickel ranged from 18.85 to 73.70% with an average of 51.58%.…”
Section: Okolie Lucky Preciousmentioning
confidence: 96%
“…Although the major constituents of fly ash are similar to those of natural soils and rocks, fly ash tends to be enriched in many trace metals (Guthrie et al, 1982;Eary et al, 1990;Mattigold et al, 1990;Gieré et al, 2003;Chaudhary and Banerjee, 2007). Furthermore, the pH dependent leaching of metal ions (e.g., arsenic, cadmium, chromium, zinc, lead, mercury, selenium) (Baba et al, 2008) raises concern regarding potential for toxic effects if contacted by aquatic receptors (Roy et al, 1981;Carlson and Adriano, 1993;Rowe et al, 2002;Kuzmick et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the recovery of silicate from the silicate material is done by acidic treatment. However, fly ash has several acid-soluble elements such as Na, K, P, Mg, Ca, and Fe [18,179], which can be present in the obtained silicate in a minute quantity [20].…”
Section: Silica Extraction From Fly Ash By Chemical Methodsmentioning
confidence: 99%